Peran Patroli Roda Empat Unit Turjawali Satuan Sabhara Dalam Mencegah Curanmor Roda Dua Di Wilayah Hukum Polres Cirebon Kota - Tony Prabowo, Hanky (Police Studies Review, 2020)
Motor vehicle theft which happens in Cirebon Kota Police Resort is trend crime than others crime that happen there. Indonesian National Police as an organization which enforce law with Sabhara as a preventive way to prevent motor vehicle theft, called police patrol. Police patrol in Cirebon Police Resort is not optimal yet, as shown that motor vehicle theft often happen. Because of that, this research is done to describe how a motor vehicle theft can happen, how police patrol can prevent a motor vehicle theft not to happen, and to identificate the factors that affect police patrol can prevent a motor vehicle not to happen. This research uses qualitative approach. This research locates in Cirebon Kota. To get the data, writer use an interview, an observation, and study documents. Writer also use a data validity check, so the the authentic of data can be guaranteed. The result of this research which is analyzed by Perkabaharkam Nomor 1 Tahun 2017 Tentang Patroli shown that police patrol is not optimal yet. Writer uses routine theory activity to analyzed how a motor vehicle theft can happen, and to analayze how police patrol and the factor, writer use Managemnt theory by George R. Terry. So as a result, the inhibitory factors are human resources, the materials, the machines, and the structural organization itself. So as the result shown above, the writer suggest to gain more members and placing the members as the competency, give target of patrol to members, train all the members, and involve community to be a police community by themselves.